OCULAR TOXICITY OF HYDROXYCHLOROQUINE IN AUTOIMMUNE RHEUMATOLOGICAL DISEASES; A TERTIARY CARE EXPERIENCE IN PAKISTAN - Faiq, Muhammad; Haroon, Muhammad; Ansari, Muhammad Sufyan Aneeq; Khan, Asad Ullah; Saeed, Muhammad Ahmed; Aslam, Muhammad Zeeshan (Journal of Postgraduate Medical Institute, 2020)
Objective: To determine the frequency of Hydroxychloroquine (HCQ) toxicity in patients suffering from autoimmune rheumatological diseases. Methodology: It was a cross sectional study conducted in Fatima Memorial Hospital from May, 2019 to July, 2019. A total of 155 patients who were taking HCQ for autoimmune diseases for more than 5 years were included. Patients with maculopathy due to other causes were excluded. Patients having renal or liver dysfunction were also excluded. Ethical clearance was obtained from institutional review board and patients fulfilling inclusion criteria were enrolled in the study after getting informed consent. Optical Coherence Topography (OCT) was performed and interpreted by consultant ophthalmologist of the hospital. Results: Mean age was 40.70 + 12.36 years ranging from 15 to 70 years. Majority, 136 (87.7%) were females. Most common disease was rheumatoid arthritis (RA) having 70 (45.2%) patients, followed by systemic lupus erythmatosus (SLE) with 60 (38.7%) patients. Bulls eye maculopathy was present in 3 (1.9%) and pre-maculopathy in 24 (15.5%) patients. Blurring of vision was reported by 28 (18.16%) patients. Mean duration of HCQ therapy was 88.26 + 40.52 months. There was no association between retinal toxicity on OCT findings and age, gender, duration of the disease, HCQ dosage and cumulative HCQ dosage (p-value 0.797, 0.808, 0.494, 0.483 and 0.749 respectively). However, duration of HCQ therapy was significantly associated with maculopathy on OCT (p-value 0.025). Conclusion: There is higher prevalence of retinal toxicity due to HCQ therapy in Pakistani population. There is a positive correlation between duration of HCQ therapy and retinal toxicity.